2011
DOI: 10.1038/ajg.2011.105
|View full text |Cite
|
Sign up to set email alerts
|

Is Refractory Celiac Disease More Severe in Old Europe?

Abstract: Refractory celiac disease (RCD) is subdivided into two subtypes (RCDI and II), based on a normal or abnormal phenotype of intraepithelial lymphocytes, respectively. RCDII is the most severe form and seems to be more frequently observed in Europe than in the United States. We discussed below the diagnostic criteria of RCDI and RCDII, and the possible factors underlying the more severe expression of celiac disease in Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Although it has been known for many years that the increased mortality in CD is due to its feared complications [23], the literature reports very few epidemiological data on these complications [8,[15][16][17][18][19]. This lack of data can undoubtedly be attributed both to the significant selection biases in these series of patients and to the difficulties caused by the lack of uniform diagnostic criteria for the various forms of CCD [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although it has been known for many years that the increased mortality in CD is due to its feared complications [23], the literature reports very few epidemiological data on these complications [8,[15][16][17][18][19]. This lack of data can undoubtedly be attributed both to the significant selection biases in these series of patients and to the difficulties caused by the lack of uniform diagnostic criteria for the various forms of CCD [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…This lack of data can undoubtedly be attributed both to the significant selection biases in these series of patients and to the difficulties caused by the lack of uniform diagnostic criteria for the various forms of CCD [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was obviously because of the lack of consensus on the definition of nonresponsiveness. 4 In the last few years, some evidence has suggested that the prevalence of RCD is low, ranging from 0.6% to 1.5%. 3,5,6 Although the presence of RCD in CD is probably to be approximately 1%, the prevalence of RCD2 among patients with RCD is far from being ascertained.…”
mentioning
confidence: 99%